2009
DOI: 10.1007/s00394-009-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Long chain saturated fatty acids increase haptoglobin gene expression in C57BL/6J mice adipose tissue and 3T3-L1 cells

Abstract: The type of lipids in the diet can differently modulate the white adipose tissue gene expression of haptoglobin, and saturated fatty acids play a major role in promoting a pro-inflammatory environment. This response is fat pad specific and dependant on the duration of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In the present study, male Wistar rats treated for 8 weeks with a lard-enriched diet (52% energy derived from fat) showed increased body and adipose tissue masses, as compared to rats fed a standard chow (15% energy from fat). These results confirm previous studies describing the effects of high fat diets as inducers of obesity in animal models and humans (16,(36)(37)(38), and the obesogenic effects of saturated fat (39,40). Several molecular mechanisms have been associated with increased adiposity induced by high fat diets, including reduced rate of dietary fat oxidation, higher lipogenesis and lower lipolysis rates, increased uptake of circulating lipids due to higher lipoprotein lipase activity (41)(42)(43), and others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, male Wistar rats treated for 8 weeks with a lard-enriched diet (52% energy derived from fat) showed increased body and adipose tissue masses, as compared to rats fed a standard chow (15% energy from fat). These results confirm previous studies describing the effects of high fat diets as inducers of obesity in animal models and humans (16,(36)(37)(38), and the obesogenic effects of saturated fat (39,40). Several molecular mechanisms have been associated with increased adiposity induced by high fat diets, including reduced rate of dietary fat oxidation, higher lipogenesis and lower lipolysis rates, increased uptake of circulating lipids due to higher lipoprotein lipase activity (41)(42)(43), and others.…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies have demonstrated the deleterious effects of saturated fat rich diets on adipose tissue fatty acid composition and endocrine function (16)(17)(18). As cell membrane phospholipids are in intimate and functional contact with executive proteins, the fatty acid composition is decisive for tissue stability and function (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking haptoglobin have increased adiponectin and are protected from HFD-induced metabolic dysfunction but have muscle atrophy 122 . Saturated fatty acids increase haptoglobin gene expression in murine adipose tissue 123 . Macrophage inflammatory gene expression in white adipose tissue is upregulated in both genetically obese and DIO mice prior to the development of insulin resistance and can be downregulated by rosiglitazone 124 .…”
Section: Macrophage and Adipocyte Dysfunction In Obese Adipose Tissuementioning
confidence: 96%
“…TNF␣ has also been implicated as a major signal for Hp induction in vitro in 3T3-L1 differentiated adipocytes (36), although there is no complete agreement on this matter and some studies report that Hp levels in human primary adipocytes were reduced following TNF␣ treatment (63,64). Factors inducing Hp expression in cultured 3T3-L1 adipocytes include also: IL-6 (65), for which the Hp promoter holds a specific response element (66), the ␤3 receptor agonists, the glucocorticoid dexamethasone, lipopolysaccharide (LPS) (36), medium and long chain saturated fatty acids (67). Hp induction in WAT by cytokines confirms the original observation by Friedrichs, according to which inflammation is a trigger for Hp also in WAT (28), but is now placed in a more complex and intriguing picture if we consider that TNF␣ and IL-6 are induced in the adipose tissue of obese subjects: Hp up-regulation is a downstream effect of this phenomenon and thus an important intersection between obesity and inflammation.…”
Section: Figurementioning
confidence: 98%